The Cambridge economic history of modern Europe. - Broadberry, S (Cambridge University Press, 2010)
Unlike existing textbooks on the economic history of modern Europe, which offer a country-by-country approach, The Cambridge Economic History of Modern Europe rethinks Europe's economic history since 1700 as unified and pan-European, with material organised by topic rather than by country. The first volume is centred on the transition to modern economic growth, which first occurred in Britain before spreading to other parts of western Europe by 1870, whilst the second tracks Europe's economic history through three major phases since 1870. Each chapter is written by an international team of authors who cover the three major regions of northern Europe, southern Europe, and central and eastern Europe. The two volumes together provide a comprehensive and accessible introduction to the key themes in modern economic history from trade, urbanisation, economic growth and business cycles to sectoral developments, and population and living standards.